2011
DOI: 10.1093/cid/cir322
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Based Loading of Vancomycin in Patients on Hemodialysis

Abstract: We evaluated weight-based loading doses of vancomycin and resulting initial prehemodialysis concentrations. Modeling demonstrated modest correlation between dose administered, age, and initial concentration achieved. Actual body weight-based loading of vancomycin predictably achieves therapeutic initial concentrations in patients who receive hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…4 Current vancomycin guidelines recommend that the trough serum concentration should be maintained between 15 and 20 mg/L for serious infections, [9][10][11] but they do not address dosing strategies or appropriate pre-hemodialysis concentration for administration of vancomycin to patients undergoing hemodialysis. 3,12 Furthermore, the recommended serum concentration of 15-20 mg/L was validated with patients who had normal kidney function, but the accuracy of this range for patients with stage 5 CKD who were receiving hemodialysis was not clearly addressed.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations
“…4 Current vancomycin guidelines recommend that the trough serum concentration should be maintained between 15 and 20 mg/L for serious infections, [9][10][11] but they do not address dosing strategies or appropriate pre-hemodialysis concentration for administration of vancomycin to patients undergoing hemodialysis. 3,12 Furthermore, the recommended serum concentration of 15-20 mg/L was validated with patients who had normal kidney function, but the accuracy of this range for patients with stage 5 CKD who were receiving hemodialysis was not clearly addressed.…”
Section: Résumémentioning
confidence: 99%
“…2,3,6,12 For instance, in various studies, different high-flux dialysis membranes removed different amounts of the drug (25% to 50%) in each dialysis session. [13][14][15][16] This variability may have been related to the differing composition of the dialysis membranes and whether or not vancomycin was infused during the last 30-90 min of dialysis.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested using loading doses of 15–20 mg/kg followed by maintenance doses of 500–1500 mg [6,26]. In a three-way randomized crossover trial conducted by Mason et al, a loading dose of 15 mg/kg resulted in a pre-hemodialysis vancomycin serum concentration of 23.8 mcg/mL ± 4.8 two days later [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, postdialysis dosing became the preferred method of vancomycin dosing in this population. The postdialysis dosing is either given during the last 30 to 90 minutes of dialysis in outpatients or after completing the dialysis session in hospitalized patients who have additional peripheral or central lines …”
Section: Introductionmentioning
confidence: 99%